Memaksimalkan Pengembangan Usaha Lewat Online - Desi Derina Yusda; Nety Kumalasari; Nisaul Khoiriah (Jurnal Multidisiplin Borobudur, 2023)
Every year, a large number of university graduates and diploma holders enter the Indonesian labor sector. When fresh high school or trade school graduates are included, the figure becomes even more astounding. Finding a job will undoubtedly become more difficult. This was entirely avoidable. If, from the start of their education, an interest in entrepreneurship was fostered so that when they graduated, they could choose to become entrepreneurs in addition to working for a company or continuing their studies (college), it is necessary to have activities to increase students' interest in entrepreneurship, namely through entrepreneurship training. The goal of this project is to see if entrepreneurship training may boost students' interest in entrepreneurship at Pelita Gedong Tataan Vocational School. If proved, the use of Entrepreneurship Development can be a solution to the problem of students' lack of interest in entrepreneurship. This instruction was offered to 39 participants, all of whom were 12th grade students from Pelita Gedong Tataan Vocational High School, and was delivered using the lecture technique.